Concept of Regional Security in Philosophical Approaches - Kononov, Sergey; Zhukov, Artem (Տիգրան Մեծ)
The paper focuses on regional security, which has becomea significantissue in situations where there has been a growth in the level of regional identity and the desire for relative autonomy in the general pro-cess of security system development. The approaches to security in the history of philosophy are analyzed in order to highlight the evolution of the concept of “regional security”. Comparative, systematic and her-meneutic methods are employed to revealthe aspects of regional security in terms of the problems of state, national and public security. The novelty of the research is associated with the development of the evolu-tion of ideas concerning regional security from abstract representations to the various aspects of regional practice. The conclusion is that modern regional security conceptsare based on the synthesis of the meth-odology of systemic and constructivist approaches. This methodology is used to substantiate the claim that any state has to deal with the security problems of its regions and pay attention to any threats and regional interests, which may be constructible in nature, and pose a real danger associated with challenges from political, economic, military, environmental, and social spheres.
Keywords: Philosophy